Processing of mature copper tailings from concentration plant using a composite reagent - L. V. Semushkina (Croatian Metallurgical Society, 2022)
The research presents the results of laboratory studies on the flotation processing of mature copper tailings using KF2 composite reagent. KF2 flotation agent is a mixture of sodium butyl xanthate, thionocarbamate, and composite aerofloat at a ratio of 1:1:3. In the base regime, a rough copper concentrate obtained had a copper content of 10,9 % with a recovery of 74,91 %. The use of KF2 composite flotation reagent increases the extraction of copper into rough copper concentrate by 5,31 %. This made it possible to obtain a rough copper concentrate with a copper content of 13,0 % and a recovery of 80,22 %. Consumption of KF2 flotation reagent is halved compared to the basic sodium butyl xanthate collector.